MENINGKATKAN LITERASI PAJAK UMKM DI KAMPUNG TUA TELUK MATA IKAN, NONGSA - BATAM - Nona Jane Onoyi; Ely Kurniawati; Diana Titik Windayati (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ibnu Sina, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, yet tax literacy amongMSMEs remains low. This community service activity aims to improve MSME tax understanding throughcommunicative and hands-on education in Kampung Tua Teluk Mata Ikan, Batam. Implementation methodsincluded observation, preparation of materials based on the latest regulations (PP 55/2022 and PMK 164/2023),interactive outreach, tax reporting simulations, and evaluation through pre- and post-tests. The activity resultsshowed a significant increase in participants' understanding of tax obligations. A down-to-earth, non-intimidatingapproach proved effective in creating a comfortable learning environment. The involvement of lecturers andstudents as facilitators also strengthened emotional bonds with participants. Challenges such as limited revenuerecording were addressed by providing simple tools. This program not only impacted tax literacy but alsoencouraged changes in attitudes toward voluntary tax compliance. These findings underscore the importance ofsynergy between universities and the community in building an inclusive and sustainable tax culture.